Contrast‐enhanced ultrasonography in dogs with inflammatory bowel disease. (25th August 2021) - Linta, Nikolina; Pey, Pascaline; Baron Toaldo, Marco; Pietra, Marco; Felici, Manuel; Bettini, Giuliano; Cipone, Mario; Diana, Alessia
Abstract: Background: Contrast‐enhanced ultrasonography (CEUS) is used to evaluate vascularity of the gastrointestinal wall in neoplastic and inflammatory diseases. Objective: To assess the feasibility of CEUS for the evaluation of duodenal perfusion in dogs with inflammatory bowel disease (IBD). Animals: Forty‐two dogs with IBD and 20 clinically healthy dogs. Methods: All CEUS studies of the duodenum were analyzed to obtain time‐intensity curves and perfusion parameters. The procedure was repeated in 12 IBD dogs 2 months after a standardized treatment. Results: On CEUS, the duodenal wall showed a typical perfusion pattern characterized by a radial and simultaneous enhancement of the wall in all dogs. On qualitative assessment, no differences were observed in contrast medium distribution between healthy and affected dogs, or between dogs with IBD before and after treatment. Peak intensity (PI) and area under the curve (AUC) significantly differed between healthy (PI = 3.58 arbitrary units [au; 1.86‐4.93 au] and AUC = 47.63 au seconds [aus, 22.68‐62.15]) and affected dogs (PI = 5.10 au [0.63‐15.16 au] and AUC = 63.62 aus [5.31‐212.20 aus]; P = .03 and .03, respectively). No significant differences were found for the perfusion parameters before and after treatment. Conclusions and Clinical Importance: We showed that CEUS allows discrimination between IBD affected dogs and healthy dogs by evaluation of time‐intensity curves, but did not provide useful information for monitoring therapeutic response. The qualitative assessment identified no significant differences between healthy and affected dogs, or between dogs before and after treatment.